Founder's political connections, second generation involvement, and family firm performance: Evidence from China - Xu, Nianhang; Yuan, Qingbo; Jiang, Xuanyu; Chan, Kam C. (Journal of Corporate Finance, 2015)
We examine whether a specialized asset of family firms, founders' political connections, influences the second generation involvement in family firms in China. We further investigate the impact of such second generation involvement on firm performance. The findings suggest that founders' political connections are a critical factor in the decision of second generation involvement, with politically connected founders more likely to appoint a second generation as a family firm chairman, CEO, or director. The results are consistent with the transfer cost hypothesis of Bennedsen et al. (2015). Moreover, we document that second generation involvement enhances firm performance, with the curtailment of tunneling as an important channel of performance improvement. Our results are robust to different empirical models and controlling for possible endogeneity issues. In addition, second-generation effects are more pronounced in firms with less outside monitoring.